Relationship between attitude, emotion and concern towards responsible ecotourism behaviour in Penang National Park, Malaysia - Ibrahim, Hayati (2022)
National parks should be able to provide economic benefits to help in wildlife conservation. However, tourism operations in Penang National Park are unable to bring economic benefits to the local community. This circumstance has put extreme pressure on the natural resources in Penang National Park as a result of illegal activities carried out there as a result of poverty and economic problems. Therefore, this study was conducted to investigate the ecotourist responsible behaviour in purchasing local products and services for wildlife conservation in Penang National Park. As environmental psychology is crucial in determining human behaviour, this study employed the Theory of Planned Behaviour to examine the relationship between attitude, emotion, and concern. This study is a quantitative research study and the data were collected cross-sectionally. Samples were obtained using the purposive sampling method and 220 set questionnaires were distributed face to face at the Penang National Park. The instrument's high internal consistency during the pilot study has led to the implementation of actual research. Statistical Software Packages, namely SPSS Amos version 26.0, were used to perform data analysis by structural equation modelling (SEM). Out of the nine hypotheses proposed, eight of them are supported. The findings of the study found that attitude towards behaviour has a significant effect on intention (H1), anticipated emotion has a significant effect on attitude and intention (H2 and H3), environmental concern has a significant effect on attitude and anticipated emotion (H4 and H6). However, the study found that environmental concern has no significant effect on intention (H5). Mediation analysis found that attitude is a mediator for the relationship between anticipated emotion and intention (H7), and attitude is also a mediator for the relationship between environmental concern and intention (H8). Mediation analysis also found that anticipated emotion is a mediator for the relationship between environmental concern and intention (H9). Theoretically, this study would add to the body of knowledge by incorporating the influence of environmental concern and anticipated emotion into the extended theory of planned behaviour (TPB). This study was the first to examine these two constructs in the extended TPB model, which has demonstrated a high level of explained variance in intention (61%). The findings of this study are critical in assisting stakeholders in the ecotourism industry to plan an effective marketing strategy in order to promote local products and services. An effective marketing strategy can attract ecotourist responsible behaviour in purchasing the local products and services that could support the local economies. Therefore, in formulating effective marketing strategies, marketers must insert elements of emotion and environmental concern in advertising or promotional tools (such as banners, posters, videos, pictures, flyers, etc.) to attract ecotourist responsible behaviour for wildlife conservation.